Paper mulberry leaves as a potential sterilant: evidence from Microtus fortis—a laboratory study - Wang, Shuangye; Chen, Junzhi; Zhao, Yunlin; Zhang, Meiwen; Zhang, Chen; He, Jianing; Wei, Lichuan; Xu, Zhenggang (Frontiers in Plant Science, 2023)
Many studies have explored the effects of different rodenticides on rodent pests worldwide. However, rodenticides usually cause secondary damage to the environment and ecosystems. Therefore, the development of new rodent chemosterilants is urgent. Considering that some compounds of paper mulberry leaves have been verified to inhibit sexual development, we aimed to explore the inhibitory effect of paper mulberry leaves on Microtus fortis. In this study, the leaves were mixed with the basal fodder of voles maintained in the laboratory. After feeding for more than one month, it was found that they wanted to increase their food intake and foraging frequency, and their weight was visibly reduced. Vole couples fed fodder mixed with leaves showed delayed reproduction and produced fewer offspring. The growth of the male testis, female uterus, and oophoron was inhibited, while no significant inhibition was observed in other organs. These results suggest that paper mulberry leaves could be a potential resource to produce chemosterilants to control vole populations by delaying their sexual growth and reproduction. If it is practical, the apparent advantages of paper mulberry are that it is an abundant resource and the inhibitory effect could be effective in both male and female individuals. Our conclusion also supports the transformation of rodent management from lethal management to fertility control, which would be more ecologically friendly to agriculture and ecosystems.